DETERMINING THE EFFICIENCY OF MASS TRAPPING OF YELLOW STICKY TRAPS IN DIFFERENT WAVELENGTHS AGAINS PISTACHIO PSYLLID IN SİİRT PROVINCE [Agonescena pistaciae Burc. and Laut. (Hemiptera: Psyllidae)] - Özgen, İnanç; Bolu, Halil; Ayaz, Tarkan; Koç, İbrahim; Mutlu, Çetin; Altun, Ayçin Aksu (My University, 2020)
This study was conducted in gardens infested with pistachio psylla in Siirt Province between 2007 and 2010. It was detected that pistachio psylla forms were the highest populations in the pistachio gardens in the Central District of Siirt Province. It causes important damages particularly on young leaves in mid-June and in the maturing period of fruits in mid- and late-August. The yellow sticky trap coded 1016 B was found to be more effective than other coded traps. It was concluded that these traps were important for decreasing of the population of the pest in cases where the population is low. It was found that traps provided positive contribution if combined with other control methods. One of the best promising results was gathered when used in 4 traps for each tree and 7-day periods of hanging.
Keywords: Entomoloji